Crafting continuity and change in Saudi society: Joint parent‐youth transition‐to‐adulthood projects. (5th January 2018) - Khalifa, Hind; Alnuaim, Aziza A.; Young, Richard A.; Marshall, Sheila K.; Popadiuk, Natalee
ABSTRACT: Little is known about the transition to adulthood in traditional, developing countries such as Saudi Arabia. Previous research in other countries has revealed the importance of considering parents' support during the transition to adulthood. Thus, the purpose of this research was to examine how two generations negotiated the transition to adulthood. We asked the research question, What are the joint projects in which parents and youth plan and act on their plans for the youth's future? We used the action project method, an established qualitative approach, to answer these questions by observing the joint conversations of 14 parent and youth dyads. Our results provided evidence of an overarching higher level goal, or intentional framework, of crafting generational change and continuity within which participants' joint projects were embedded. Joint projects were organized into three groups: (a) negotiating educational and career futures, (b) promoting gender roles and marriage, and (c) shaping independence.